Carbohydrate amphiphiles for supramolecular biomaterials: design, self-assembly, and applications - Brito, Alexandra Manuela Fernandes (2021)
Carbohydrate-containing biopolymers such as glycoproteins, proteoglycans, and glycolipids are an incredibly diverse and complex set of natural building blocks used by biological systems to endorse a wide range of molecular functions that are critical to life processes. Simplified synthetic analogs of these polymeric glycoconjugates can capture some of these functions and are increasingly exploited toward the development of supramolecular biomaterials. These carbohydrate amphiphiles can mimic structural aspects through cooperative molecular self-assembly or target distinct signaling pathways through engineered (multivalent) interactions with biological systems. Herein, we discuss the supramolecular principles that regulate the glycome function(s) and the translation of these in the design of supramolecular biomaterials in which carbohydrates are used as information-rich structural elements with huge potential as therapeutic supramolecular biomaterials.